Overview Of Characteristics, IPSS Score, and Quality of Life BPH Patients in Mataram Hospital - Samudera, I Made Ari; Nandana, Pandu Ishaq (Faculty of Medicine Universitas Mataram, 2020)
Overview of Characteristics, IPSS Score, and Quality of Life BPH Patient’s in Mataram Hospital I Made Ari Samudera1 Pandu Ishaq Nandana2 Abstract Background: Benign prostate hyperplasia (BPH) is a degenerative disease that causes discomfort. Risk factors; are; age, obesity, and diabetes mellitus (DM). Patients can be assessed by using the International Prostate Symptom Score (IPSS) which contains seven questions and one Quality of Life (QoL) question. This study aims to describe some risk factors for BPH, IPSS score and QoL scores. Method: This study used a descriptive cross-sectional design. The sample was 43 BPH patients in Mataram City Hospital. The research instrument used medical records, measuring instruments for height and weight, and reference values for IPSS score and QoL scores on PPK BPH IAUI. Result: This study found that the ages of 70-79 years were 44.1%, 60-69 years 37.2%, ? 80 years 11.6%, and 50-59 years 6.9%. Patients with DM 18,6 % and non DM 81,4 %. Patients with obesity 27.9% while non-obese 72.1%. IPSS score moderate category was 44.1%, severe 39.5% and mild 16.2%. The highest QoL score was 4 with 27.9% patients, while the lowest QoL score was 0 with 2.3% patient. Conclusion: BPH patients in Mataram Hospital were dominated 44.1% from aged 70-79 years, non-DM 81,4 %, and non-obese 72.1%. IPSS score is dominated by the moderate category 44.1%, with a QoL score of 4 with 27.9%. Keywords: BPH, Ages, DM, Obesity, IPSS score, QoL Score 1Internship in Mataram Hospital *e-mail: arisamudera@yahoo.com